Fecal Occult Blood Test and Gastrointestinal Parasitic Infection - Majed H. Wakid (Journal of Parasitology Research, 2010)
Stool specimens of 1238 workers in western region of Saudi Arabia were examined for infection with intestinal parasites and for fecal occult blood (FOB) to investigate the possibility that enteroparasites correlate to occult intestinal bleeding. Direct smears and formal ether techniques were used for detection of diagnostic stages of intestinal parasites. A commercially available guaiac test was used to detect fecal occult blood. 47.01% of the workers were infected with intestinal parasites including eight helminthes species and eight protozoan species. The results provided no significant evidence (P-value=0.143) that intestinal parasitic infection is in association with positive guaiac FOB test.